Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.3390/ijerph17072484
|View full text |Cite
|
Sign up to set email alerts
|

‘Get a Fish’ vs. ‘Get a Fishing Skill’: Farmers’ Preferred Compensation Methods to Control Agricultural Nonpoint Source Pollution

Abstract: Ecological compensation is an important means for controlling agricultural nonpoint source pollution, and compensation methods comprise an essential part of the compensation policy for mitigating this form of pollution. Farmers’ choice of compensation methods affects their response to compensation policies as well as the effects of pollution control and ecological compensation efficiency. This study divides ecological compensation methods into two distinct philosophies—the “get a fish” method (GFM) and “get a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…Younger rural families with higher family incomes, perceptions of ecological benefits, and perceptions of government policies are more willing to participate in compensation policies. Li et al (2020) found that rice farmers prefer "get fish" to "get a fishing skill" compensation methods. Although these studies inform policymakers' incentive compensation schemes (including standards and methods) for farmers to improve the allocation efficiency of These studies helped to design compensation mechanisms for a specific measure, but they cannot exchange the priorities of various governance measures within the CRB framework.…”
Section: Introductionmentioning
confidence: 99%
“…Younger rural families with higher family incomes, perceptions of ecological benefits, and perceptions of government policies are more willing to participate in compensation policies. Li et al (2020) found that rice farmers prefer "get fish" to "get a fishing skill" compensation methods. Although these studies inform policymakers' incentive compensation schemes (including standards and methods) for farmers to improve the allocation efficiency of These studies helped to design compensation mechanisms for a specific measure, but they cannot exchange the priorities of various governance measures within the CRB framework.…”
Section: Introductionmentioning
confidence: 99%